Variety of Expressions of Arrogance in The Qur’an - Zaini, Muhammad (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
The problem in this paper is the number of expressions used by the Qur'an to refer to the word arrogant, namely takabburan, marahan, 'uluwwan, 'utuwwan, ashiru, jabbāran, and mukhtālan, which are different expressions in terms of words but have the same meaning, namely arrogance. This raises the question,